Increased 18F-ALF-NOTA-FAPI and 18F-FDG Uptake in Renal Angiomyolipoma. (13th March 2022) - Guo, Yue-Hong; Yang, Min-Fu
Abstract: Angiomyolipoma is a common benign tumor in the kidney. Previous publication reported that renal angiomyolipoma had very low to low uptake of 18 F-FDG. We report a case of pathologically proven angiomyolipoma in the left kidney with intense 18 F-FDG and 18 F-ALF-NOTA-FAPI uptake.